(untitled) (KASBIT Business Journal, 2026)
The climate change threat to humanity occupies the top position on the global agenda. The sustainable growth notion has captured great attention worldwide to formulate policies for human survival. This research paper analyses the association of CO2 emissions with total natural resources rents while also incorporating other control variables for Pakistan for the time period of 1971 – 2020. The quantile autoregressive distributed lag (QARDL) model is used to evaluate the cointegration linkage of the variables. The findings of this study confirm the existence of asymmetries and nonlinearities in the long run relationship for energy consumption and total natural resources rents. Energy consumption has stronger deteriorating effect on the environment, therefore it is recommended to impose more tax on non-renewable energy sources. Natural resources could help to achieve sustainable development targets by vertical integration of manufacturing and energy sectors.